2022
DOI: 10.3390/foods11192989
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Young Taiwanese Consumers’ Acceptance, Sensory Profile, and Drivers of Liking for GABA Oolong Tea Beverages with Cold Infusions

Abstract: The sensory qualities of Taiwanese teas are evaluated by the experts from the Tea Research and Extension Station (TRES) at tea competitions held annually. The prices of Taiwanese teas are also influenced by the results of these tea competitions. However, a tea winning an award and having a high sensory quality and price does not mean that it is liked by Taiwanese consumers. The check all that apply method (CATA) is a scientific method of sensory evaluation. It is able to evaluate the sensory characteristics wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The other constituents of GABA tea produced from these four areas had varying differences, and there were no distinct trends in these differences. Wu et al (2022) reported that the sensory quality of GABA tea primarily differs based on the manufacturer rather than being influenced by factors such as production areas and seasons [24]. In this study, it was observed that GABA tea produced in high-mountainous areas had higher GABA content on average.…”
Section: Physico-chemical Constituents Of Gaba Teamentioning
confidence: 58%
See 1 more Smart Citation
“…The other constituents of GABA tea produced from these four areas had varying differences, and there were no distinct trends in these differences. Wu et al (2022) reported that the sensory quality of GABA tea primarily differs based on the manufacturer rather than being influenced by factors such as production areas and seasons [24]. In this study, it was observed that GABA tea produced in high-mountainous areas had higher GABA content on average.…”
Section: Physico-chemical Constituents Of Gaba Teamentioning
confidence: 58%
“…But the results of the tea competition in Taiwan usually affect the quality and price of the tea. The award-winning tea selected by the judges does not reflect that it will be liked and purchased by consumers [24]. The consumer acceptance test is the most appropriate way to understand how consumers feel about food and the willingness of consumers to buy it [25].…”
Section: Introductionmentioning
confidence: 99%